Validity and Practicality of Manarang Module Based on Preservice Mathematics Teachers - Wardani, Sri; Mira, Mira; Nurtaqiya, Nurtaqiya; Anaguna, Nursyam (Griya Journal of Mathematics Education and Application, 2025)
This research aims to develop and evaluate the validity and practicality of the Manarang module, an innovative digital teaching module based on ethnomathematics and Augmented Reality (AR) designed for prospective mathematics teacher students. This study employs the Borg and Gall model research and development methodology, which includes restricted trials, expert validation, initial product development, and planning. 32 students enrolled in the University of West Sulawesi's mathematics education studies program served as the study's subjects. Student response surveys to gauge practical features and validation sheets from media and material experts are among the research tools. The results of the study showed that the Manarang module was declared very valid with an average validation score of 90.67% for media experts and 90% for material experts. Furthermore, the practicality test resulted in an average score of 87.07 which falls into the category of very practical. These results show that the developed e-modules are valid, practical, and feasible to use as an innovative learning medium that not only presents mathematical concepts interactively and contextually through the integration of local cultures, but also utilizes AR technology to visualize abstract concepts to make them easier to understand. The Manarang module will help prospective teachers visualize geometric objects in geometric transformation learning.